Using Mathematics Conferences in the Classroom (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2019)
There has been frequent research on the benefits of using reading conferences in the English Language Arts classroom and how to make those valuable reading conferences as effective as possible.  However, there has been little research on how researchers and teachers can take that information and transfer it into the mathematics classroom.  This paper looks at the research on effective reading conferences in English Language Arts and proposes how to transfer that information to supporting successful mathematics conferences by looking at specific, research-based strategies.  It also discusses how mathematics conferences can help address current difficulties in mathematics instruction and how to incorporate mathematics conferences into the classroom.